Philosophy in Economics
X, 212 p.
Keywords: The essays in this volume are the result of a workshop held at Virginia Polytechnic Institute and State University in April, 1979. The assembled group was diverse, comprised of philosophers, economists, and statisticians. But it was not the complete group on which we had initially planned. Richard Rudner was in France on sabbatical and was unable to fly back for the occa sion. His untimely death the following summer saddened us all, for we lost not just a colleague but a friend. This book is dedicated to him out of the spirit of friendship and in appreciation for the ground breaking work he did in the philosophy of the social sciences. In addition to the participants, a number of people worked very hard to make our gathering possible. We are especially indebted to Dean Henry Bauer, Dean Ernie Stout and Dean John Ballweg of the College of Arts and Sciences at Virginia Tech for their good will and support, both moral and substantive. We would also like to thank Professor Guy Hammond, Head, Department of Philosophy and Religion, for his council and assistance. Our special thanks to Jeanne Keister and Betty Davis for their patience with unending typing and reservations, and finally to Barbara Kersey, always at hand, ever helpful. Without them nothing would have transpired.